Production of Siamenoside I and Mogroside IV from Siraitia grosvenorii Using Immobilized β-Glucosidase - Hung-Yueh Chen; Ching-Hsiang Lin; Chih-Yao Hou; Hui-Wen Lin; Chang-Wei Hsieh; Kuan-Chen Cheng (Molecules, 2022)
Siraitia grosvenorii is a type of fruit used in traditional Chinese medicine. Previous studies have shown that the conversion of saponins was often carried out by chemical hydrolysis, which can be problematic because of the environmental hazards it may cause and the low yield it produces. Therefore, the purpose of this study is to establish a continuous bioreactor with immobilized enzymes to produce siamenoside I and mogroside IV. The results show that the immobilization process of β-glucosidase exhibited the best relative activity with a glutaraldehyde (GA) concentration of 1.5%, carrier activation time of 1 h and binding enzyme time of 12 h. After the immobilization through GA linkage, the highest relative activity of β-glucosidase was recorded through the reaction with the substrate at 60 °C and pH 5. Subsequently, the glass microspheres with immobilized β-glucosidase were filled into the reactor to maintain the optimal active environment, and the aqueous solution of Siraitia grosvenorii extract was introduced by controlling the flow rate. The highest concentration of siamenoside I and mogroside IV were obtained at a flow rate of 0.3 and 0.2 mL/min, respectively. By developing this immobilized enzyme system, siamenoside I and mogroside IV can be prepared in large quantities for industrial applications.